AUTHORIZATION AND APPROPRIATION: AN IMPLEMENTATION OF CONGRESS’ POWER OF THE PURSE - Kwiatkowski, Wojciech (Zeszyty Prawnicze, 2024)
This article discusses the origins, fundamental principles, and procedures used by the United States Congress in the mechanisms of budget authorization and appropriation. The model in which the federal legislature decides severally to allocate specific amounts for designated purposes and release specific amounts at shorter intervals for the implementation of those purposes, while publicly monitoring progress in their achievement, appears to be an eﬀective tool for the control of expenditure. The article also addresses several issues concerned with the implementation of statutory provisions regarding authorization and appropriation. The current procedures give rise to chronic problems with passing the budget within the prescribed timeframe, which all too often may lead to a “temporary shutdown” of the federal government. Such notorious incidents not only ridicule the United States but primarily undermine its credibility and creditworthiness, challenging the generally acknowledged virtues of American parliamentary democracy and the ability of the American political class to strive for compromise.